Review of 113 cases of autoimmune disorders in pregnancy - S., Maheswari; C., Poornima; Panicker, Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Autoimmune disorders are chronic multisystem disorders affecting women of their reproductive age. Pregnancy among these women is complicated by the disease itself. Flaring up of disease, uteroplacental insufficiency due to vasculitis and drugs used for treatment are main reason for unfavourable pregnancy outcomes. The objective of this study was to analyze the pregnancy complications and outcome among 113 cases of autoimmune disorders. Methods: This study is a retrospective analysis of case records of pregnant women with autoimmune disorders. This study was conducted at PSG IMSR and Hospital, Coimbatore, and Tamil Nadu from July 2012 to June 2018. The case sheets were retrieved from medical record department and the details such as type of disease, maternal age, parity, status of disease at conception, treatment taken during pregnancy, maternal complications and fetal complications were collected and analyzed. Results: During 6-year period there were 113 pregnant women with autoimmune disorders, and they were studied of their previous and present pregnancy outcome. The disease incidence was 7.01% per 1000 deliveries. 40.7% were less than 25 years age group and 71.6% were multigravidae. We had forty-one patients (36%) who were positive for APLA syndrome which were the maximum number of patients with auto immune disorder in pregnancy and 37 patients (32.7) with SLE. We had significant numbers of maternal and fetal complications for common disorders. Most of the rare auto immune disorders were diagnosed before pregnancy and these pregnancies were managed by multi-disciplinary approach, and continued on immunomodulators throughout pregnancy, hence maternal and fetal complications were less for them. Conclusions: Adequate pre-conceptional counseling, vigilant monitoring during pregnancy and post-partum will avoid pregnancy related complications and have favorable outcomes.